Preparation and Characterization of MKT-077 Nanoparticles for Treatment of Alzheimer’s Disease and Other Tauopathies - K. Jinwal, Umesh; Grover, Aditya; Narayan, Malathi; Hirani, Anjali; Sutariya, Vijaykumar (Pharmaceutical Nanotechnology, 2014)
Alzheimer’s disease is one of the most common causes of dementia and death in elderly populations. However, therapeutic intervention in Alzheimer’s disease is limited by the blood-brain barrier, which not only protects the brain by limiting the permeation of potential toxins into neural tissue but also by blocking certain drugs aimed at neurological disorders. MKT-077 is one such drug, which has shown promise in reducing Alzheimer’s disease- related pathology in cellular models but has limited brain permeation due to blockage by the blood-brain barrier. Herein, we describe the formulation and characterization of brain-targeted PEG-PLGA nanoparticles coated in 2% w/v glutathione to get higher blood-brain barrier permeation. Average nanoparticle size was found to be 230nm, suitable for intravenous administration and brain permeation. The nanoparticles showed steady, sustained release of MKT-077 in in vitro settings. Transwell in vitro blood-brain barrier model permeation studies showed the permeation of nanoparticles across the Transwell model to be greater than drug solution over 48 hours. The proposed model shows promise as a potential therapy against Alzheimer’s disease and other tauopathies.
Keywords: tau protein